Book reviews: Faith in an age of terror. Edited by Quek Tze Ming and Philip E. Satterthwaite. Singapore: Genesis Books, 2018, pp.150. ISBN: 978- 981-48-0707-4 - Aminudin, Rabi'ah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This book is timely considering that the beginning of the 21st century is marked by the tragedy of 9/11 which witnessed the most heinous act of terrorism committed in the land of democracy. This tragedy has changed the discourse on religion and terrorism and continues to be discussed by scholars. Experts are interested to explore the role of religion especially Christianity and Islam in the age where religious fundamentalism has been closely linked to violent acts. The book contains nine chapters that are based on papers presented at the conference on ‘Faith in an Age of Terror’ organised by the Biblical Graduate School of Theology(BGST), Singapore.